MODL-19. DIPG HARBOUR ALTERATIONS TARGETABLE BY MEK INHIBITORS, WITH ACQUIRED RESISTANCE MECHANISMS OVERCOME BY COMBINATORIAL UP- OR DOWN-STREAM INHIBITION. (4th December 2020) - Izquierdo, Elisa; Carvalho, Diana; Mackay, Alan; Temelso, Sara; Boult, Jessica K R; Molinari, Valeria; Stubbs, Mark; Depani, Sarita; O'Hare, Patricia; Robinson, Simon P; Hubank, Michael; Hargrave, Darren; et al.
Abstract: The survival of children with DIPG remains dismal, with new treatments desperately needed. In the era of precision medicine, targeted therapies represent an exciting treatment opportunity, yet resistance can rapidly emerge, playing an important role in treatment failure. In a prospective biopsy-stratified clinical trial (BIOMEDE), we combined detailed molecular profiling (methylation BeadArray, exome, RNAseq, phospho-proteomics) linked to drug screening in newly-established patient-derived models of DIPG in vitro and in vivo . We identified a high degree of in vitro sensitivity to the MEK inhibitor trametinib (GI50 16-50nM) in samples which harboured genetic alterations targeting the MAPK pathway, including the non-canonical BRAF _G469V mutation, and those affecting PIK3R1 . Treatment of PDX models and the patient with trametinib at relapse, however, failed to elicit a significant response. We generated trametinib-resistant clones (62-188-fold, GI50 2.4–5.2µM) in the BRAF _G469V model through continuous drug exposure, and identified acquired mutations in MEK1/2 ( MEK1 _K57N, MEK1 _I141S and MEK2 _I115N) with sustained pathway up-regulation. These cells showed the hallmarks of mesenchymal transition, with overexpression of key proteins involved in invasion/migration, such as collagen-family proteins, integrins, MMPs and AHNAK2, amongst others. Resistant clones were conversely sensitive to the upstream receptor tyrosine kinase inhibitor dasatinib (GI50 36-93nM), and combinations of trametinib with dasatinib and the downstream ERK inhibitor ulixertinib showed synergistic effects in vitro . These data highlight the MAPK pathway as a therapeutic target in DIPG, and show the importance of parallel resistance modelling and rational combinatorial treatments likely to be required for meaningful clinical translation.